2020
DOI: 10.1089/vio.2019.0054
|View full text |Cite
|
Sign up to set email alerts
|

Baltimore's Underground Gun Market: Availability of and Access to Guns

Abstract: Underground gun markets can create opportunities for individuals who are prohibited from gun ownership to gain access to guns. Understanding how these individuals obtain guns, and their unsuccessful attempts to get guns, is key to developing interventions that effectively restrict the supply of guns in an underground market. We conducted surveys of criminal justice-involved men (n = 195) in Baltimore City about their experiences in the underground gun market, of whom 30% reported having any experience in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…In the study, forty of the forty-eight primary firearms referenced had been obtained from family members, fellow gang members, or other social connections (Cook, Parker, and Pollack 2015). Baltimore parolees reported similar patterns in 2020; among offenders reporting efforts to obtain firearms in the previous six months, 53 percent reported encountering difficulties (Crifasi et al 2020). Increased efforts to disrupt these local networks are essential to adding friction to the supply of firearms in underground markets.…”
Section: Underground Markets: Supply-side Insights For Policy-makersmentioning
confidence: 97%
See 2 more Smart Citations
“…In the study, forty of the forty-eight primary firearms referenced had been obtained from family members, fellow gang members, or other social connections (Cook, Parker, and Pollack 2015). Baltimore parolees reported similar patterns in 2020; among offenders reporting efforts to obtain firearms in the previous six months, 53 percent reported encountering difficulties (Crifasi et al 2020). Increased efforts to disrupt these local networks are essential to adding friction to the supply of firearms in underground markets.…”
Section: Underground Markets: Supply-side Insights For Policy-makersmentioning
confidence: 97%
“…The resulting patchwork of federal, state, and local regulations is fertile ground for a thriving national underground firearm market, which supplies most firearms used in interpersonal crimes (Braga et al 2012(Braga et al , 2021Cook, Parker, and Pollack 2015;Hasegawa, Webster, and Small 2019;Webster and Wintemute 2015). Like other markets, the underground firearm trade responds to supply-and demand-side pressures and shocks, as well as incentives and constraints (Braga et al 2021;Cook, Parker, and Pollack 2015;Cook, Pollack, and White 2019;Crifasi et al 2020).…”
Section: Underground Firearm Marketsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some federally licensed firearm (FFL) dealers may be directly involved in the supply of guns to prohibited purchasers. Evidence suggests that certain gun shop employees may sell guns off the record or make sales to known straw purchasers (Crifasi et al., 2020). In a survey of criminal justice‐involved men in Baltimore, 31% of those who were active in the underground gun market said that they knew of gun shops where employees sold guns off the books or did not require background checks (Crifasi et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that certain gun shop employees may sell guns off the record or make sales to known straw purchasers (Crifasi et al., 2020). In a survey of criminal justice‐involved men in Baltimore, 31% of those who were active in the underground gun market said that they knew of gun shops where employees sold guns off the books or did not require background checks (Crifasi et al., 2020). Other studies of handgun dealers have revealed some willingness to assist potential handgun buyers with a “straw” purchase or purchases employees understood to be against the law (Sorenson & Vittes, 2003), particularly among pawnbrokers (Wintemute, 2010).…”
Section: Introductionmentioning
confidence: 99%